Predictive modeling of turn success probability for "between the lines" play in football - Koizumi, H.; Nakayama, M. (Japan Journal of Physical Education, Health and Sport Sciences, 2025)
The purpose of this study was to identify the main factors influencing the success to receive and turn with the ball "between the lines" in football and to construct a regression equation to predict turn success probability. The sample consisted of 1,260 plays in which a pass was received "between the lines" at the 2018 FIFA World Cup held in Russia. The play data was collected using game performance analysis. In the statistical processing, the main factors influencing turn success probability in the "between the lines" of football were clarified using logistic regression analysis. The factors influencing the success probability of a turn were the presence or absence of visual exploratory activity, the type of pass, i.e., a grounder, a bound, or a lob, the receiver`s position, the distance from receiver to first defender at the moment of receiving the pass, the distance to the first midfielder, the distance from receiver to first defender at the moment of passer`s passing, the distance to the first midfielder, the pressing speed of the first defender, the pressing speed of the first midfielder, the pass distance, the pass angle, the pass speed, and the number of forward-looking players present between the lines. In addition, a regression equation was constructed to predict turn success probability by combining the odds ratios of the main factors. It was verified that the regression equation can be used to predict turn success probability in the "between the lines" with high accuracy (accuracy rate 77.1%). Future work includes using the regression equation to clarify the usefulness of turn success probability from comparative verification with the performance made after the turn.